Mengembangkan Literasi Bagi Calon Pendidik Dalam Menghadapi Era Revolusi Industri 4.0 Melalui PBL Berbasis Kehidupan - Mintasih, Diah (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2022)
Changes in the world are now entering the era of industrial revolution 4.0, where the pattern of human life is based on information. Thus, preparing graduates who are qualified and able to compete globally, and master the development of technology are important for everyone and important for the future of a country. This article examines the strategy of developing information literacy through PBL's integrated life-based learning to prepare prospective educators in the face of the 4.0 industrial revolution era. In detail it reveals the study includes (a) information literacy, (b) research skills, (c) life-based learning, (d) integrated PBL learning, and, (e) capability of prospective educators, and (f) era of Industrial Revolution 4.0